UPAYA MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA MATERI TEKS EKSPLANASI DI KELAS VIII SMP SWASTA AL-WASHLIYAH 1 MEDAN - Balqis, Fauziah (CV Sintesia, 2024)
This study aims to determine the increase in student learning outcomes with the application of the model Problem Based Learning (PBL). The low student learning outcomes can be caused by teachers still use conventional methods and learning is still teacher-centered. This research is a classroom action research held in 2 cycles. Each cycle is carried out 2 times the meeting began with the stages of action planning, implementation of action model Problem Based Learning (PBL), and reflection. Method of data collection is done by class observation and test. Data analysis was performed by the comparison between the results of the test in cycle 1 and cycle 2 with the techniques of descriptive. While to measure the learning achievement of students with percentage of classical completeness in the results of the evaluation of each cycle. The results showed that the learning outcomes of students of class VIII SMP Swasta Al Washliyah 1 Medan has increased. In cycle 1 classical completeness is 67,74% dan in cycle 2 classical completeness is 87,10%. The results in cycle II showed that the learning of explanation text by using the model of Problem Based Learning (PBL) on students of class VIII SMP Swasta Al Washliyah 1 Medan can improve student learning outcomes.